Dynamics of Granular Flows Down Rotating Semi-cylindrical Chutes. (2015) - Shirsath, S.S.; Padding, J.T.; Clercx, H.J.H.; Kuipers, J.A.M.
Abstract: The behavior of spherical particles flowing down a three-dimensional chute, inclined at fixed angle, is commonly simulated by a discrete element method (DEM). DEM is nowadays a standard tool for numerical studies of e.g. gas-solid fluidized beds. We have modified DEM for the simulation of rotating granular flows. In view of future extensions aimed at, for example, segregation studies of (rotating) bi- and polydisperse granular flows or mixtures of two kinds of granular particles with different densities, several validation steps are required. In a first step we compare DEM simulations with experiments of monodisperse spherical glass particles flowing through a rotating semi-cylindrical chute inclined at a fixed angle and constant flow rate. Different measurement techniques such as Particle Image Velocimetry and Particle Tracking Velocimetry are used to measure the averaged surface velocity of the particles and the bed height in the chute. We observe that the prevailing flow patterns depend strongly on the rotation rate of the chute. The streamwise and the spanwise particle velocities are influenced by the centrifugal and Coriolis forces, where with increasing rotation rate the particles are moving increasingly sideways. We find that the details of the particle feeding pattern are important only for the particle flow near the entrance of the chute, whereas after a relatively short distance the particle flow depends only on other factors such as the mass rate, inclination angle and rotation rate. Our DEM model predictions agree well with the experimental measurements for bed height and surface velocity.